Rock Pressure Characteristics and Control Technology of Underground Roadways during Stacked Coal Seam Extraction - Futian Nian (Advances in Civil Engineering)
Ensuring the stability of underground structures during the extraction of stacked coal seams is imperative for the sustainable exploitation of coal resources. This study investigates the influence of stacked coal seam extraction on the integrity of nearby underground roadway structures. It employs a comprehensive methodology combining on-site measurements, physical experimentation, and numerical simulations, with particular emphasis on the 23513 transport roadway as the primary research focus. The results delineated a specific stress distribution on the goaf area floor, with reduced stress at the edges and heightened stress centrally. Additionally, the roadway’s roof exhibited pronounced stress variability, with a maximum stress concentration coefficient of 5.5. The surrounding rock of the roadway was found to be susceptible to structural integrity breakdown, leading to delamination and zone-based deterioration, which significantly extended the plastic zone. To mitigate these issues, a novel high pretension thick-layer anchoring control technique was introduced. This method significantly enhanced support strength, refined support procedures, and entailed a bespoke design of support plan parameters. Industrial-scale on-site trials confirmed the efficacy of this technique, with a separation value of the top plate of 4–10 mm, achieving effective management of the surrounding rock deformation in the roadway, with crack development contained within the fundamental anchoring layer. The implementation of this technique ensured the safety of the roadway and offered substantial insights for the governance of similar conditions in other roadways.